Inpatient Ambulation: Use of an Ambulation Platform Apparatus. (June 2015) - Henecke, Lorrie; Hessler, Karen L.; LaLonde, Trent
Abstract : Ambulation has proven to be an important part of recovery for medical-surgical patients. This study provides original research on the use of a platform apparatus for ambulation of patients on a medical-surgical unit. Outcomes included number of ambulation attempts, distance of ambulation, length of hospital stay, number of staff necessary to ambulate, and discharge destination. Compared with a control group, patients who had access to the ambulation platform apparatus had a shorter length of stay with fewer nurses and other staff needed to ambulate. Staff rated ambulation with the apparatus as easier than without and noted that patients were more willing to ambulate on their own with the ambulation platform apparatus. Abstract : Supplemental Digital Content is available in the text.